Das Schloss als Zeichen des Aufstiegs Die Ausstattung von Vaux-le-Vicomte im Kontext repräsentativer Strategien des neuen Adels im französischen 17. Jahrhundert - Müller, Marion (Höfische Kultur interdisziplinär (HKi) - Schriften und Materialien des Rudolstädter Arbeitskreises zur Residenzkultur, 2022)
Louis XIV's absolutist rule, which began in 1661, was preceded by a period of intensive building activity of ascended state and financial elites in France. Among the most important of these estates, which were mostly located in the Parisian countryside, was the château of Vaux-le-Vicomte (built for Nicolas Fouquet), which serves as a case study for the interaction between social mobility and art. This volume focuses on the decoration of the château and garden, created under the direction of Charles Le Brun between 1657 and 1661, and places it in the context of comparable decoration projects of the time.